Praktik Menunda Perkawinan Sebab Menuntut Ilmu Perspektif Maslahat dan Mafsadah - Syaifuddin, Ahmad Masruh; Latifah, Hanik (Al-Mawaddah: Jurnal Studi Islam dan Hukum Keluarga (Ahwal Al-Syakhsiyyah), 2025)
This study aims to examine the practice of delaying marriage among santri (Islamic boarding school students) at Pesantren At-Tahdzib Jombang through the lens of Islamic law. This phenomenon arises from the students’ conscious choice to prioritize the pursuit of knowledge—both formal and informal—before entering marital life. The research employs a qualitative approach with a case study method. Data were collected through in-depth interviews with eight unmarried santri aged 21 to 28, and analyzed using the Islamic legal principles of maslahat (benefit) and mafsadah (harm). This research employs a qualitative approach using a case study method. The study was conducted at Pesantren At-Tahdzib Jombang. Data were collected through in-depth interviews with eleven selected santri and pesantren administrators aged 21 to 28 who were unmarried. Participants were purposively chosen based on their experience in delaying marriage for the sake of pursuing religious education. The data were analyzed descriptively using the Islamic legal principles of maslahat (benefit) and mafsadah (harm). The study concludes that delaying marriage for the sake of seeking knowledge is justifiable in Islamic law, provided it is based on sincere intentions and accompanied by self-discipline. Such postponement is a conscious effort to achieve greater long-term benefits, both personally and socially.